High‐dose intravenous immunoglobulin is strongly associated with hemolytic anemia in patients with Kawasaki disease. Issue 11 (28th September 2018) - Nolan, Brian E.; Wang, Yunfei; Pary, Philippe P.; Luban, Naomi L.C.; Wong, Edward C.C.; Ronis, Tova
Abstract : BACKGROUND: Hemolysis is a reported side effect of intravenous immunoglobulin (IVIG) therapy in adults, but pediatric data are scarce. We determined the frequency of IVIG‐associated hemolysis in patients with Kawasaki disease (KD) and characterized risk factors for hemolysis. We hypothesized that hemolysis is more common in children with KD than adults with other disorders, and hemolysis risk is related to IVIG dose and degree of inflammation. STUDY DESIGN AND METHODS: This was an 8‐year, single‐center, retrospective cohort study. A total of 419 KD patients were identified; 123 had pre‐ and post‐treatment complete blood counts allowing for assessment of anemia. Hemolytic anemia was defined as decrease in hemoglobin after IVIG greater than 1 g/dL with immunohematologic or biochemical studies supporting hemolysis. RESULTS: 123 patients were stratified as having hemolysis (n = 18, 15%) or nonhemolysis (n = 105, 85%). Patients with hemolysis were more likely to have complete versus incomplete KD (65% vs. 39%, p = 0.04) and refractory versus nonrefractory course (78% vs. 16%, p < 0.001). Patients receiving 4 g/kg versus 2 g/kg IVIG were more likely to hemolyze (89% vs. 34%, p < 0.001). Patients with hemolysis had mostly non‐O blood group (94%), positive direct antiglobulin tests (89%), and positive eluates (72%). Two‐thirds of patients with hemolysis required RBC transfusion. CONCLUSIONS: Hemolysis occurred in 15% of KD patients evaluated for anemia and is strongly associated with high‐dose (4 g/kg) IVIG. KD patients receiving high‐dose IVIG should have close hematologic monitoring to identify hemolysis.